A theory of fields - Fligstein, Neil.; McAdam, Doug. (New York ; London : Oxford University Press, 2012)
In recent years there has been an outpouring of work at the intersection of social movement thoery, organizational theory economic, and political sociology. The problems at the core of these areas, Fligstein and McAdam argue, have a similar analytic and theoretical structure.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Change; Stability; Social movements